Grassland management impacts on soil carbon stocks: a new synthesis - Conant, Richard T.; Cerri, Carlos E. P.; Osborne, Brooke B.; Paustian, Keith (Ecological applications, 2017)
Grassland ecosystems cover a large portion of Earths' surface and contain substantial amounts of soil organic carbon. Previous work has established that these soil carbon stocks are sensitive to management and land use changes: grazing, species composition, and mineral nutrient availability can lead to losses or gains of soil carbon. Because of the large annual carbon fluxes into and out of grassland systems, there has been growing interest in how changes in management might shift the net balance of these flows, stemming losses from degrading grasslands or managing systems to increase soil carbon stocks (i.e., carbon sequestration). A synthesis published in 2001 assembled data from hundreds of studies to document soil carbon responses to changes in management. Here we present a new synthesis that has integrated data from the hundreds of studies published after our previous work. These new data largely confirm our earlier conclusions: improved grazing management, fertilization, sowing legumes and improved grass species, irrigation, and conversion from cultivation all tend to lead to increased soil C, at rates ranging from 0.105 to more than 1 Mg C·ha⁻¹yr⁻¹. The new data include assessment of three new management practices: fire, silvopastoralism, and reclamation, although these studies are limited in number. The main area in which the new data are contrary to our previous synthesis is in conversion from native vegetation to grassland, where we find that across the studies the average rate of soil carbon stock change is low and not significant. The data in this synthesis confirm that improving grassland management practices and conversion from cropland to grassland improve soil carbon stocks.